Apakah Profitabilitas dipengaruhi Oleh Non Performing Loans dan Capital Adequacy Ratio? Apakah Profitabilitas dipengaruhi Oleh Non Performing Loans dan Capital Adequacy Ratio? - Temmy; Agus Munandar (Accounting Profession Journal (APAJI), 2025)
ABSTRACT Examining how Non-Performing Loans and Capital Adequacy Ratio affect profitability is the aim of this study. This study uses banks published on the IDX in 2024 as the population, sample of the research was originated using a purposive sampling approach. The data sought for this research is secondary and sourced from the bank’s annual reports from 2020 to 2023. For evaluating the influence of NPL and CAR on Profitability, writer used multiple linear regression, and for assessing quality of the variables, used classical assumption test. The result of the statistical test reveal that NPL and CAR have simultaneous bearing on profitability. NPL has an opposing impact on Profitability and CAR doesn’t impact profitability. Keyword: NPL, CAR, Profitability, Annual report, Bank